1986
DOI: 10.1128/iai.54.2.568-574.1986
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, biological, and immunochemical properties of the Chlamydia psittaci lipopolysaccharide

Abstract: The lipopolysaccharide (LPS) of Chlamydia psittaci was extracted from yolk sac-grown elementary bodies, purified, and characterized chemically, immunochemically, and biologically. The LPS contained Dgalactosamine, D-glucosamine, phosphorus, long-chain fatty acids, and 3-deoxy-D-manno-2-octulosonic acid in the molar ratio of approximately 1:2:2:6:5. The antigenic properties of the isolated LPS were compared with those of the LPS from Chiamydia trachomatis and Salmonella minnesota Re by the passive hemolysis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(42 citation statements)
references
References 32 publications
2
40
0
Order By: Relevance
“…One should keep in mind that even minor contamination with proteins, lipoproteins or nucleic acids may be relevant in the sensitive assays available today. Nevertheless, there is good evidence from our group [10] and others [11] that chlamydial LPS is less active than typical enterobacterial LPS in classical endotoxin assays. When we decided to investigate the biological activity of chlamydial LPS in more detail we wanted to base this study on preparations whose structures had been characterized fully.…”
Section: Discussionmentioning
confidence: 85%
“…One should keep in mind that even minor contamination with proteins, lipoproteins or nucleic acids may be relevant in the sensitive assays available today. Nevertheless, there is good evidence from our group [10] and others [11] that chlamydial LPS is less active than typical enterobacterial LPS in classical endotoxin assays. When we decided to investigate the biological activity of chlamydial LPS in more detail we wanted to base this study on preparations whose structures had been characterized fully.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, synthetic peptides have been used recently to determine antibodies against the major outer membrane protein in patients suffering from trachoma [12]. Our group has accumulated knowledge on the chemical [19,20,22] and antigenic [15,18,19,24] structure of chlamydial LPS, and has developed reagents suitable to be used in simple antibody-detection assays [26,32,33,35]. In particular, the synthesis of artificial glycoconjugates with chemically defined carbohydrate ligands allowed us to determine the epitope specificities of poly-and monoclonal antibodies [15,26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be a multifunctional glycosyl-transferase catalyzing three glycosylation steps [21] leading to the formation of a trisaccharide of 3-deoxy-o-manno-octulosonic acid (Kdo) of the sequence aKdo-(2 8)-aKdo-(2-~ 4)-c~Kdo [19,20,22]. The a2 ~ 4linked disaccharide portion of the trisaccharide is identical to that of enterobacterial Re-mutants [23] and forms the molecular basis for cross-reactions between chlamydial and Re-type LPS [15,24,25]. In addition, we have shown that synthetic artificial glycoconjugate antigens containing this epitope bind specifically mAbs against chlamydial LPS [22,26].…”
Section: Introductionmentioning
confidence: 99%
“…Three fractions were obtained, eluting between sodium acetate concentrations of 255 -273 mM (tetrasaccharide bisphosphate l), 318-347 mM (mixture of two pentasaccharide bisphosphates 2 and 3), and 393-420 mM (hexasaccharide bisphosphate 4). These compounds were desalted by gel-permeation chromatography and lyophilised (tetrasaccharide bisphosphate: 48.3 mg, 19.6mg GlcN, 7.2% total LPS; mixture of pentasaccharide bisphosphates: 124.2 mg, 41.5 mg GlcN, 15.2% total LPS; hexasaccharide bisphosphate: 72.7 mg, 19.7 mg GlcN, 7.2% total LPS). Analytical HPAE revealed one compound each for the tetrasaccharide and hexasaccharide bisphosphate, and two compounds for the pentasaccharide bisphosphate mixture.…”
Section: Methodsmentioning
confidence: 99%